2011
DOI: 10.1037/a0021914
|View full text |Cite
|
Sign up to set email alerts
|

On personality and piloerection: Individual differences in aesthetic chills and other unusual aesthetic experiences.

Abstract: Relatively little is known about aesthetic chills, the experience of goose bumps and shivers in response to the arts. The present study explored how often people report such experiences and what people who often experience them are like. After noting which domain of the arts they encountered most often in daily life, young adults (n ϭ 188) rated how often they experienced aesthetic chills and related states. Latent variable models suggested three latent factors-aesthetic chills, feeling touched, and absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
165
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(176 citation statements)
references
References 41 publications
9
165
1
1
Order By: Relevance
“…Silvia and Nusbaum's (2011) finding that Extra version and Neuroticism were both positively related to the chills gains theoretical significance in this light. Extraversion also emerged as a significant predictor in exploratory analyses by Rickard (2004).…”
Section: Trait Antecedentsmentioning
confidence: 88%
See 1 more Smart Citation
“…Silvia and Nusbaum's (2011) finding that Extra version and Neuroticism were both positively related to the chills gains theoretical significance in this light. Extraversion also emerged as a significant predictor in exploratory analyses by Rickard (2004).…”
Section: Trait Antecedentsmentioning
confidence: 88%
“…Nusbaum and Silvia (2011) found that Openness to Experience was the only Big Five trait that predicted self-reports of chills frequency, and Silvia and Nusbaum (2011) reported that the "openness" subscale of an Openness to Experience measure predicted self-reports of chills frequency. Silvia and Nusbaum also found that chills frequency was predicted negatively by the intellect subscale of Openness to Experience, positively by Extraversion and Neuroticism subscales, and negatively by a Conscientiousness subscale.…”
Section: Trait Antecedentsmentioning
confidence: 98%
“…Also included in the questionnaire was the Short Test of Musical Preferences (STOMP) . The prevalence of intense emotional responses to music was assessed based on the answers to the Aesthetic Experience Scale in Music (AES-M), which consists of 15 questions derived from the Aesthetic Experience Scale (Sloboda, 1991;Silvia and Nusbaum, 2011). The list of questions contained in the AES-M can be found in Appendix A in the Supplementary materials available online.…”
Section: Participant Screeningmentioning
confidence: 99%
“…Sloboda19 found that different musical features are associated with either tears or chills. By using a multivariate statistical method, Silvia and Nusbaum20 showed that peak emotional responses to art have multiple dimensions. Furthermore, a study of ‘being moved’ suggested that tears and chills involved different factors21.…”
mentioning
confidence: 99%